Incidence of diarrhoea and household diarrhoea management among children of integrated child development services in Buldhana district of Maharashtra - Ingle, Sagar; Nagdeve, Deveram (International Journal Of Community Medicine And Public Health, 2023)
Background: Adequate water and sanitation facilities are crucial in promoting good child health. Unfortunately, many children lack access to these resources. Thus, this study aimed to investigate the prevalence of diarrhoea among children and the household-level management of diarrhoea. Methods: The study utilized both qualitative and quantitative methods, quantitative analysis involved selecting a total of 300 samples using the stratified random sampling method. Twenty key informants were interviewed conducted to qualitative study. Results: The study found that, the prevalence of diarrhoea among ICDS children 24.5 percent. However, this prevalence varied depending on several factors, including gender, caste, education, occupation, and wealth. The findings highlighted the importance of a mother's education in preventing and addressing diarrhoea within the household. Additionally, the availability of improved water resources played a crucial role in the prevalence of diarrhoea, as a significant portion of the population had limited access to such resources. Unfortunately, many mothers lacked sufficient knowledge about diarrhoea, negatively impacting their children's health. Mothers commonly relied on traditional methods to manage diarrhoea, which could result in additional health complications for their children. Conclusions: Providing access to safe drinking water from a single source can help to reduce cases of diarrhoea. Overall, improving education, increasing access to clean water, and promoting better hygiene practices are essential steps to preventing and managing diarrhoea effectively.